Effect of Elasticity on Viscoplastic Flow - Letelier-Sotomayor, M; Siginer, D (American Society of Mechanical Engineers, 2016)
The effect of superimposing elasticity on a viscoplastic fluid (elasto-viscoplastic fluid) is investigated through a linear combination of the simplified Phan-Thien Tanner (SPTT) model of viscoelasticity and Bingham model of viscoplastic fluid. The equation of motion is solved for the case of parallel steady flow in tubes of non-circular cross-sections. The effect of elasticity on the evolution of plug and stagnant zones, and rate of flow in terms of the Weissenberg number, a material parameter in the SPTT model, and the Bingham number is investigated. We find that elasticity tends to enhance the rate of flow for given viscoplastic conditions. Copyright © 2016 by ASME.